+0  
 
0
316
1
avatar+4676 

Help.

 Dec 1, 2017

Best Answer 

 #1
avatar+7352 
+1

-3x4 + 27x2 + 1200  =  0

 

First, let's divide each term by  -3  .

 

x4 - 9x2 - 400  =  0

 

Now, notice that we can write  x4  as  (x2)2 .

 

(x2)2 - 9x2 - 400  =  0

 

And this factors as...

 

(x2 - 25)(x2 + 16)  =  0            Set each factor equal to zero.

 

x2 - 25  =  0          or          x2 + 16  =  0

x2  =  25               or           x2  =  -16

 

Now we can solve each equation for  x  by taking the ± square root of both sides.

 

x  =  ± 5          or          x  =  ± 4i

 

So all the zeros are   5 ,  -5 ,  4i , and  -4i

 Dec 1, 2017
 #1
avatar+7352 
+1
Best Answer

-3x4 + 27x2 + 1200  =  0

 

First, let's divide each term by  -3  .

 

x4 - 9x2 - 400  =  0

 

Now, notice that we can write  x4  as  (x2)2 .

 

(x2)2 - 9x2 - 400  =  0

 

And this factors as...

 

(x2 - 25)(x2 + 16)  =  0            Set each factor equal to zero.

 

x2 - 25  =  0          or          x2 + 16  =  0

x2  =  25               or           x2  =  -16

 

Now we can solve each equation for  x  by taking the ± square root of both sides.

 

x  =  ± 5          or          x  =  ± 4i

 

So all the zeros are   5 ,  -5 ,  4i , and  -4i

hectictar Dec 1, 2017

26 Online Users

avatar
avatar